(untitled) (Journal of Hama University, 2021)
This research is concerned with the study of “the mythical symbol and its artistry in the poetry of Mahmoud Darwish " who is considered one of the most important Arab poets. The mythical symbol is an important stylistic feature, and it is interesting to consider modern and contemporary Arabic poetry in general and Darwish’ s poetry in particular. The legend is one of the best aesthetic expressive tools that the poet Mahmoud Darwish resorted to, and he used it in his poetry.By means of it, he was able to portray reality in literary images distinguished by its artistic and aesthetic expression, as his mythical culture is so deep that he was able to transform the myth into an essential part of the structure of the poem.This research comes in an introduction, three sections and a conclusion. In the first section we explained the concept of the symbol and the myth, and in the second section we dealt with ancient heritage myths such as the legend of the phoenix, the myth of Tammuz and Ishtar, the Gilgamesh myth, and the symbolism of each myth and its connotations. As for the third topic entitled “Innovative Myths in Mahmoud Darwish’s Poetry,” Mahmoud Darwish created new symbols and employed them in his poems, which then turned into mythological symbols that have their significance and meanings, from these symbols : the month of March , Ahmad al-Zaatar , the symbol of bread.We concluded the research with a conclusion, in which we mentioned the most important findings of the research, then a list of sources and references.